APLAR rheumatoid arthritis treatment recommendations - Chak Sing Lau (2018)
© 2015 Asia Pacific League of Associations for Rheumatology and Wiley Publishing Asia Pty Ltd. Aims: Rheumatoid arthritis is a chronic inflammatory condition that affects approximately 1% of the world's population. There are a wide number of guidelines and recommendations available to support the treatment of rheumatoid arthritis; however, the evidence used for these guidelines is predominantly based on studies in Caucasian subjects and may not be relevant for rheumatoid arthritis patients in the Asia-Pacific region. Therefore, the Asia Pacific League of Associations for Rheumatology established a Steering Committee in 2013 to address this issue. Materials and methods: The AGREE II instrument and the ADAPTE Collaboration framework were applied to systematically identify, appraise, synthesize, and adapt international rheumatoid arthritis guidelines for use in the Asia-Pacific region. Results: Forty rheumatoid arthritis treatment recommendations, based on evidence and expert opinion, were drafted and are presented in this report. Conclusion: The Asia Pacific of Associations for Rheumatology rheumatoid arthritis treatment recommendations are intended to serve as a reference for best practice management of rheumatoid arthritis in Asia-Pacific, focusing on local issues to ensure the delivery of basic care for these patients, and to improve their outcomes. In addition, the document will serve as a reference for national rheumatology associations in Asia-Pacific for developing guidelines in their respective countries. International Journal of Rheumatic Diseases